The Effect of Entrepreneurial Knowledge, Industrial Work Practices (Internship), and Family Environment on Entrepreneurial Readiness Through Self-Efficacy - Renaningtyas, Dwi Lestari; Wahyudin, Agus; Khafid, Muhammad (Journal of Economic Education, 2021)
This study aims to find out the effect of entrepreneurial knowledge, industrial work practices, and family environment on entrepreneurial readiness through self-efficacy as the mediation variable. The population in this study were 568 students of the Agribusiness Expertise Program for Agricultural Product Processing for class XI and XII of Public Vocational School (SMK Negeri) Jepara Regency in the 2018/2019 academic year and a sample of 235 students was obtained with the Slovin formula with a standard error of 5%. This study used questionnaires as data collection tools. The data analysis used descriptive analysis, path analysis, and Sobel test. The results showed that 1) There was a positive and significant effect of entrepreneurial knowledge on entrepreneurial readiness (32.2%), 2) There was a positive and significant effect of industrial work practices on entrepreneurial readiness (23.7%), 3) There was a positive and significant effect of family environment on entrepreneurial readiness (14.3%), 4) There was a positive and significant effect of self-efficacy on entrepreneurial readiness (19.4%), 5) There was a positive and significant effect of entrepreneurial knowledge on self-efficacy (31.3%), 6) There was a positive and significant effect of industrial work practices on self-efficacy (16.2%), 7) There was a positive and significant effect of family environment on self-efficacy (11.5%), 8) There was a positive and significant effect of entrepreneurial knowledge (38.3%), industrial work practices (26.8%), and family environment (16.5%) on entrepreneurial readiness through self-efficacy as the mediating variable. Based on these results, it can be concluded that self-efficacy is proven could be a mediating variable for the effect of entrepreneurial knowledge, industrial work practice, and family environment on students' entrepreneurial readiness